Political analysis a guide to data & statistics - Loveless, Matthew (SAGE Publications Ltd, 2023)
From news reporting on elections or unfolding political crises to everyday advertising, you are confronted with statistics. Rather than being swayed by bad arguments and questionable correlations, this book introduces you to the most common and contemporary statistical methods so that you can better understand the world. It's not about mindless number crunching or flashy techniques but about knowing when to use statistics as the best means to analyse a problem"--